The value of chest magnetic resonance imaging compared to chest radiographs with and without additional lung ultrasound in children with complicated pneumonia - Konietzke, Philip; Wünnemann, Felix; Wagner, Willi Linus; Schenk, Jens-Peter; Alrajab, Abdulsattar; Kauczor, Hans-Ulrich; Stahl, Mirjam; Mall, Marcus A.; Wielpütz, Mark Oliver; Sommerburg, Olaf (PLOS ONE, 2020)
Introduction: In children with pneumonia, chest x-ray (CXR) is typically the first imaging modality used for diagnostic work-up. Repeated CXR or computed tomography (CT) are often necessary if complications such as abscesses or empyema arise, thus increasing radiation exposure. The aim of this retrospective study was to evaluate the potential of radiation-free chest magnetic resonance imaging (MRI) to detect complications at baseline and follow-up, compared to CXR with and without additional lung ultrasound (LUS). Methods: Paired MRI and CXR scans were retrospectively reviewed by two blinded readers for presence and severity of pulmonary abscess, consolidation, bronchial wall thickening, mucus plugging and pleural effusion/empyema using a chest MRI scoring system. The scores for MRI and CXR were compared at baseline and follow-up. Furthermore, the MRI scores at baseline with and without contrast media were evaluated. Results: 33 pediatric patients (6.3±4.6 years), who had 33 paired MRI and CXR scans at baseline and 12 at follow-up were included. MRI detected significantly more lung abscess formations with a prevalence of 72.7% compared to 27.3% by CXR at baseline (p = 0.001), whereas CXR+LUS was nearly as good as MRI. MRI also showed a higher sensitivity in detecting empyema (p = 0.003). At follow-up, MRI also showed a slightly better sensitivity regarding residual abscesses. The overall severity of disease was rated higher on MRI. Contrast material did not improve detection of abscesses or empyema by MRI. Conclusion: CXR and LUS seem to be sufficient in most cases. In cases where LUS cannot be realized or the combination of CXR+LUS might be not sufficient, MRI, as a radiation free modality, should be preferred to CT. Furthermore, the admission of contrast media is not mandatory in this context.